Peran Guru Bimbingan dan Konseling dalam Membantu Meningkatkan Mengelola Emosi Peserta Didik yang Orang Tuanya Broken Home - Mudaim Mudaim; Agus Wibowo; Putu Wina Meilani (Universitas Muhammadiyah Metro, 2021)
In this study, the focus of research is directed at the role of guidance and counseling teachers in helping students improve emotional management. Based on the focus of the problem above, the formulation of the research problem is: How is the emotional management of students whose parents are broken homes? What is the role of BK teachers in helping to improve the ability to manage emotions in students whose parents are broken homes? This research method uses qualitative research with descriptive research type. The presence of researchers as research data collectors as well as analyze data. The instrument in this study used interview sheets, observations, and documentation. Data analysis used descriptive inductive data analysis. The results of this study concluded that: Management of students' emotions before the role and intervention of guidance and counseling teachers, the condition of emotional management was still less than optimal. This is marked by students who have not been able to overcome the volatile emotions within themselves, are less able to control emotions, still have negative thoughts, stress, and withdraw from association. The role of the guidance and counseling teacher in helping to improve the emotional management of students is that the guidance and counseling teacher always acts as a guide, counselor, friend, advisor, and motivator for students. Through this role, the emotional management of students slowly improves well.